2018
DOI: 10.24167/psidim.v17i2.1664
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Student-Teacher Trust with School Well-Being to High School Students

Abstract: This research is a correlational study using quantitative method of distributing questionnaires to students of class X, XI and XII in X Senior High School in the area of West Jakarta and Y Senior High School in North Jakarta. Student-teacher trust questionnaire refers to Tchannen-Moran’s study, while school well-being questionnaire refers to Konu and Rimpelä’s study. The research is using purposive sampling technique involving 486 students. The results of the study shows that student-teacher trust has a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Specifically, empirical studies have found trust in the university setting to increase collaboration between student and school (Mitchell, Kensler & Tschannen-Moran, 2018;Abdelmaaboud, Peña, & Mahrous, 2020), academic performance (Ennen, Stark & Lassiter, 2015;Latif, Bunce, & Ahmad, 2021), healthy school climates and quality school life (Hongwidjojo, Monika & Wijaya, 2018;Jones & Afnan, 2019), collective teacher efficacy (Flood & Angelle, 2017), triadic set of interactions and academic optimism (Cansoy & Parlar, 2018), and student identification with school (Mitchell, Kensler, & Tschannen-Moran, 2018).…”
Section: Trust In University Settingmentioning
confidence: 99%
“…Specifically, empirical studies have found trust in the university setting to increase collaboration between student and school (Mitchell, Kensler & Tschannen-Moran, 2018;Abdelmaaboud, Peña, & Mahrous, 2020), academic performance (Ennen, Stark & Lassiter, 2015;Latif, Bunce, & Ahmad, 2021), healthy school climates and quality school life (Hongwidjojo, Monika & Wijaya, 2018;Jones & Afnan, 2019), collective teacher efficacy (Flood & Angelle, 2017), triadic set of interactions and academic optimism (Cansoy & Parlar, 2018), and student identification with school (Mitchell, Kensler, & Tschannen-Moran, 2018).…”
Section: Trust In University Settingmentioning
confidence: 99%
“…Concerning hope in L2 contexts, research signifies that it is correlated with achievement, performance, self-esteem, career behavior, satisfaction, cognitive ability, success, resilience, confidence, self-efficacy, wellbeing, and engagement ( Hirschi, 2014 ; Feldman and Kubota, 2015 ; Gallagher et al, 2017 ). Likewise, trust in L2 settings has been found to influence teachers’ professional learning, fairness, wellbeing, engagement, job satisfaction, psychological empowerment, and classroom rapport ( Hoy and Tarter, 2004 ; Khany and Tazik, 2016 ; Hongwidjojo et al, 2018 ; Bellibaş and Gümüş, 2021 ). Both hope and trust can play a significant role in the development of grit in that when EFL teachers are hopeful and have trust in their colleagues and organizations, they manage the encountering setbacks better and become more gritty.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…It is an interpersonal and context-bound state that forms the cornerstone of education, engagement, and success ( Hoy and Tarter, 2004 ). It has been found to influence classroom rapport, fairness, justice, wellbeing, work engagement, satisfaction, psychological empowerment, and task accomplishment ( Tschannen-Moran and Hoy, 1998 ; Hoy and Tarter, 2004 ; Khany and Tazik, 2016 ; Hongwidjojo et al, 2018 ). Moreover, it can be argued that both hope and trust can contribute to and pave the way for EFL teachers’ sense of grit.…”
Section: Introductionmentioning
confidence: 99%
“…Discussions about school well-being were investigated in several settings, including at, among others, students of State Vocational Schools (Andriany & Setyawan, 2016), Pharmacy Foundation Vocational School (Nanda & Widodo, 2015), college students (Rizki & Listiara, 2015), middle school students (Abdillah et al, 2020), high school student (Wahidah & Royanto, 2019) (Hongwidjojo et al, 2018) (Evans et al, 2018) (Ramberg et al, 2019), Christian high school students (Imelda, A., & Wahyuningrum, 2017). In this study, it will be focused on the setting of Muhammadiyah Vocational High School Students because vocational secondary education is a secondary education level that prioritizes the development of students' abilities to carry out certain types of work, which is expected after graduates of Muhammadiyah Vocational Schools students have competencies according to the needs of the world of work and have a noble character so that in this study focused on students of SMK Muhammadiyah.…”
Section: Theoritical Frameworkmentioning
confidence: 99%